Peripheral Neuropathic Pain: From Experimental Models to Potential Therapeutic Targets in Dorsal Root Ganglion Neurons - Ti-Yen Yeh (Cells, 2020)
Neuropathic pain exerts a global burden caused by the lesions in the somatosensory nerve system, including the central and peripheral nervous systems. The mechanisms of nerve injury-induced neuropathic pain involve multiple mechanisms, various signaling pathways, and molecules. Currently, poor efficacy is the major limitation of medications for treating neuropathic pain. Thus, understanding the detailed molecular mechanisms should shed light on the development of new therapeutic strategies for neuropathic pain. Several well-established in vivo pain models were used to investigate the detail mechanisms of peripheral neuropathic pain. Molecular mediators of pain are regulated differentially in various forms of neuropathic pain models; these regulators include purinergic receptors, transient receptor potential receptor channels, and voltage-gated sodium and calcium channels. Meanwhile, post-translational modification and transcriptional regulation are also altered in these pain models and have been reported to mediate several pain related molecules. In this review, we focus on molecular mechanisms and mediators of neuropathic pain with their corresponding transcriptional regulation and post-translational modification underlying peripheral sensitization in the dorsal root ganglia. Taken together, these molecular mediators and their modification and regulations provide excellent targets for neuropathic pain treatment.